2003
DOI: 10.1080/07315724.2003.10719306
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Triglyceride Catabolism: Implications for the Hemodynamic Model of the Metabolic Syndrome

Abstract: Elevated blood pressure per se and hypertension-related hemodynamic and vascular alterations are not associated with reduced TG K(2) or other metabolic abnormalities. Rather, aspects of the insulin resistance syndrome are closely related to abdominal adiposity. The independent association between small vessel compliance and TG K(2) deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Image analyses were performed using semi-automated software (Medical Imaging Applications, Inc). Arterial compliance was measured by radial artery tonometry using the CVProfilor as described before (Hypertension Diagnostics, Inc) 18 .…”
Section: Methodsmentioning
confidence: 99%
“…Image analyses were performed using semi-automated software (Medical Imaging Applications, Inc). Arterial compliance was measured by radial artery tonometry using the CVProfilor as described before (Hypertension Diagnostics, Inc) 18 .…”
Section: Methodsmentioning
confidence: 99%
“…Natural oil occurring lipophilic antioxidants (e.g. vitamin E, beta-carotene, lavonoids, monoterpene, terpenoids) inhibited the oxidative modi ication of low-density lipoproteins [73][74][75][76][77][78][79][80]. Studies showed that they could possibly prevent atherogenesis and coronary heart diseases.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The exact mechanism whereby the metabolic syndrome influences vascular outcome is unknown. It is thought that the constituents of metabolic syndrome may perpetuate increased vascular risk through mechanisms including insulin resistance, [43][44][45][46] hypercoaguability, 47 endothelial dysfunction, 48 and inflammation. 31 Biomarkers of vascular risk including C-reactive protein (CRP) are elevated in children, adolescents, and adults with the metabolic syndrome.…”
Section: Possible Mechanisms Underlying the Metabolic Syndromementioning
confidence: 99%